Ruehssia bahiensis: a new species of Apocynaceae endemic to a floristically neglected area within the Semi-arid of Bahia, Brazil - Oliveira, Ilana C.; Santo, Fábio S. Espírito; Rapini, Alessandro; Dórea, Marcos C.; Oliveira, Reyjane P. (Phytotaxa, 2023)
Ruehssia belongs to the Apocynaceae, tribe Marsdeniae, including all neotropical species of this family with erect pollinia. This genus includes about 110 species, 44 of which occur in Brazil. In recent floristic surveys conducted within the Semi-arid region of Bahia state, Northeast Brazil, a new species of Ruehssia was recognised, which is herein described and illustrated. It resembles R. pickelii (Fontella & Morillo) F.Esp.Santo & Rapini, known from the caatinga vegetation in Pernambuco, Paraíba and Rio Grande do Norte states, but has the corolla lobes adaxially pubescent (vs glabrous), corona lobes shorter than (vs as high as) the gynostegium and an exserted, conical (vs inserted and subglobose) style-head apex. The newfound species is named R. bahiensis and is known from only three locations, two within the “sisal territory” and one in the region of Feira de Santana. All these locales are floristically underexplored and have undergone an extensive transformation into pasture and agricultural land.